2007
DOI: 10.1093/jn/137.6.1528s
|View full text |Cite
|
Sign up to set email alerts
|

3-Dimensional Structures of G Protein-Coupled Receptors and Binding Sites of Agonists and Antagonists

Abstract: We summarize here recent progress in predicting the 3-dimensional (3D) structure of G protein-coupled receptors (GPCR) and in predicting the binding sites for various agonists and antagonists. These receptors play a critical role in cell communications (dopamine, histamine, epinephrine, and serotonin) and in sensing the outside world (vision, smell, taste, and pain). There are no experimental 3D structures available for human GPCR despite their vital function and importance as therapeutic targets. Indeed, cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 32 publications
4
35
0
Order By: Relevance
“…The results reported here are comparable to those from other similar works [19][20][21][22] which showed that GPCR modeling [23][24][25][26][27][28][29][30][31] in the absence of a crystal structure can be a valid replacement [32][33][34][35][36][37][38][39] for structural and functional exploration of GPCR receptors, and for the discovery [21,[40][41][42][43], VS [44][45][46][47][48][49][50][51][52] and optimisation [23,53] of their ligands.…”
Section: Introductionsupporting
confidence: 90%
“…The results reported here are comparable to those from other similar works [19][20][21][22] which showed that GPCR modeling [23][24][25][26][27][28][29][30][31] in the absence of a crystal structure can be a valid replacement [32][33][34][35][36][37][38][39] for structural and functional exploration of GPCR receptors, and for the discovery [21,[40][41][42][43], VS [44][45][46][47][48][49][50][51][52] and optimisation [23,53] of their ligands.…”
Section: Introductionsupporting
confidence: 90%
“…Unlike most nonolfactory GPCRs, which use ionic or hydrogen bond interactions to ensure selectivity and sensitivity in binding their agonists or antagonists (22), ORs bind to their ligands via much weaker van der Waals interactions (14,16,23). It is conceivable that at least some ORs have a permissive binding The total response is the sum of the responses to all five odorants at 300 μM, normalized to that of WT MOR256-3 tested on the same plate and corrected for surface expression.…”
Section: Discussionmentioning
confidence: 99%
“…Chitobiose units were then docked into the two binding sites, determined by unbiased scanning of the OmpA receptor (see supplemental Methods) using our GenDock procedure (32). GenDock has been validated to predict accurate binding sites in previous studies (33)(34)(35)(36)(37)(38). Here, we generated Ͼ2,000,000 ligand poses and selected the best pose based on the ligand interaction energy with the binding pocket.…”
Section: Methodsmentioning
confidence: 99%